Accumulation and Translocation of Micro-Nutrients in Soil and Plants of Orchard and Non-Orchard Fields: Translocation of Micro-nutriants in Soil - Khan, Nazish Huma; Nafees, Mohammad; Saeed, Tooba; Khan, Abdullah; Bashir, Adila (Biological Sciences - PJSIR, 2020)
The present study was conducted in the Plum orchard zone of district Peshawar. The study was aimed to investigate the levels of different micronutrients in the orchard soil and crop in corresponding to non-orchards. For this purpose, samples of soil and seasonal crop (wheat crop) were collected from both orchard and non-orchard fields. The collected samples were analyzed for various metals such as Mn, Fe, Cu, Zn, Cd, Cr, Ni and Co through Atomic Absorption Spectrophotometer. The results showed that in orchard soils, mean concentrations of Mn (486.9 mg/Kg), Cu (81.66 mg/Kg), Cd (2.21 mg/Kg), Cr (54.2 mg/Kg) and Ni (27.9 mg/Kg) were observed above their allowable limits. Similarly, in orchard wheat crops, a higher accumulation of Fe (416.1 mg/Kg), Cu (18.6 mg/Kg), Cr (1.5 mg/Kg) and Cd (0.63 mg/Kg) was calculated in the wheat grain/seed part. In non-orchards, all metals were found at safe levels. Analysis of the irrigation water revealed higher limits of Mn (0.06 mg/L), Fe (1.94 mg/L), Cd (1.29 mg/L), Cr (3.14 mg/L) and Ni (1.23 mg/L). Geo-accumulation Index showed a moderate and heavy level of contamination in orchard soils (Igeo. <1, 2). Higher uptakes of Mn (0.81) and Cu (0.87) were calculated in wheat crops of orchards through Transfer Factor (TF). Based on the observations, it is concluded that metals enrichment in orchard fields can be attributed due to excessive applications of fungicide sprays, fertilizers and contaminated water sources that introduce trace-elements into the soil and are subsequently absorbed by plants. Therefore, it is considered important to take appropriate measures to monitor the soils, crops and water for different micronutrients.